Economic viability of different tapping systems in rubber tree clones - Silva, Juliano Quarteroli; Souza, Mario Ivo Tavares de; Gonçalves, Paulo de Souza; Aguiar, Adriano Tosoni da Eira; Gouvêa, Lígia Regina Lima; Pinotti, Raquel Nakazato (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate yield performance and economic aspects of three clones of rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell. Arg.], in different tapping systems. The trial was placed under randomized blocks design with split-plot in time. The main treatments were PR 255, RRIM 600 and GT 1 clones submitted to nine systems of tapping: ½S d/3 6d/7.11m/y.ET 2,5% Pa La 8/y; ½S d/3 6d/7.11m/y.ET 5,0% Pa La 8/y; ½S d/4 6d/7.11m/y.ET 2,5% Pa La 8/y; ½S d/4 6d/7.11m/y.ET 5,0% Pa La 8/y; ½S d/5 6d/7.11m/y.ET 2,5% Pa La 8/y; ½S d/5 6d/7.11m/y.ET 5,0% Pa La 8/y; ½S d/7 6d/7.11m/y.ET 2,5% Pa La 8/y; ½S d/7 6d/7.11m/y.ET 5,0% Pa La 8/y and ½S d/2 6d/7.11m/y (check). The variables were: girth increment, dry rubber productivity and brown bast. The economic viability of the tapping systems was also evaluated. Economical benefits in the ½S d/3.ET 2,5% 8/y system for PR 255 and RRIM 600 clones and in the ½S d/7.ET 2,5% 8/y system for GT 1 clone were observed, compared with the check. Highest and smaller incidence of brown bast were observed in the ½S d/3.ET 5,0% 8/y and ½S d/7.ET 5,0% 8/y systems, respectively.